Transverse magnetic field effects on diamond quantum sensor for EV battery monitor - Hatano, Yuji; Tanigawa, Junya; Nakazono, Akimichi; Sekiguchi, Takeharu; Kainuma, Yuta; Abe, Hiroshi; Onoda, Shinobu; Ohshima, Takeshi; Iwasaki, Takayuki; Hatano, Mutsuko (Frontiers in Quantum Science and Technology, 2024)
Key implementation points for achieving full accuracy in simultaneous temperature and magnetic field measurement and linearity when applying diamond quantum sensors to electric vehicle (EV) battery monitors were investigated. Both the static and busbar current magnetic field are required to be aligned to the NV-axis. If misalignment should exist, the resonance frequency midpoint move in the direction opposite to the temperature change under a large busbar current due to the transverse magnetic field effect. Misalignment could be quantified with an accuracy of ±1° by analysing the resonance frequency midpoint change under a current of ±1000 A. The transverse magnetic field effects compensation estimated from misalignment, confirmed that the resonance frequency midpoint changed consistently with temperature changes. Furthermore, linearity over a wide dynamic range also improved. Moreover, it will contribute to accurate alignment of the two sensors for differential detection to eliminate external noise as common mode. These are expected to expand the application of diamond sensors for high-precision measurement in a wide dynamic range.